Flavored mashed banana (nilupak na saging) production in Barangay Sampaloc Tanay, Rizal - Figuracion, Danica L.; Manaligod, Patricia Ann J.; Setubal, Mary Joy R.; Viray, K. C. Lyn F.; Suarez, Euselle P. (2018)
Management and Personnel Feasibility The proponents of this project are Danica L. Figuracion, Patricia Ann J. Manaligod, Mary Joy R. Setubal and K. C. Lyn F. Viray, who will act as Industrialist/Capitalist partners. The name of the establishment will be Nilupak King, which is obviously named under the proposed product. The proponents agreed to venture into partnership. There will be five personnel. The general manager must prioritize the monitoring of daily operation of the business and tasks, projects and demands and responsible to develop marketing strategy and to take charge of customer's order. Production workers are responsible in maintaining the quality of products through following good manufacturing practices. The driver also receives order from the managers and responsible in delivering the products on time at the scheduled places. Marketing Feasibility The proposed business will be a distributor in the following school around Brgy Sampaloc. Private: ABCAI, Greenfield Montessori, Gratia Divina school, Highland Park, Mind Care and Asian Hope Christian Academy, Public: University of Rizal System Main Campus, Sampaloc National Highschool, Sampaloc Elementary School, Camp Capinpin Elementary School . The business will be located at Signal Village Sampaloc Tanay, Rizal, where most of the people tend to pass and also near at schools. It will also aimed to provide an exceptional and innovative goods through a reliable production system with the future oriented understanding under the changes and developing condition of the environment with a reasonable pricing system. Specific strategies for the target market the marketing mix (pricing, place, people, product and promotion) and marketing budget that contains the computation for the beginning of the business. Production Feasibility The proponents desire to expand and offer something different out of nilupak product, thus, a kakanin product which will be known for its several health benefits such as high fiber content, boost heart health, ease digestion, cures ulcers, fight anemia, aids weight loss. Likewise, banana provides energy and power for the brains, Mashed banana will be made up 90 percent natural. The production of the mashed banana can be distributed into 140 boxes (large) and 20 boxes (small) equivalent of 160 boxes every eight (8) hours per production, for (5) days a week from Monday to Friday equivalent to twenty (20) days in a month. Financial Feasibility The partners will invest an equal amount for this project to be utilized in the operation of the business to reach the initial capital required amounting to PhP540,677.11 which constitutes all the necessary expenses for the month which include permits and licenses; purchase of machinery, equipment, furniture and tools, cost of materials needed for the renovation of the area that will be incurred in the preparation of the business. Table 20 presents the measurement of the firm capacity to earn sufficient return in sales, total assets and owners investment. Profit Income Ratio of 0.30, indicates that for every PhP1.00 sales. There is a Net Income of PhP0.30 pesos and its continuously increasing for every succeeding year of operation. Rate on Return on Assets of 0.81 indicates that every PhP1.00 assets of the company to generate revenue, it yielded PhP0.81 of net income. Rate on Equity of 0.81 signifies that, for every PhP1.00 of invested capital by the owners and used to generate revenue, it yielded, PhP0.81 of net income. Return on Investment of 4.07 implies that, for every PhP1.00 of investment PhP4.07 pesos will earn it means that the firm is very much capable of paying its fixed interest charges from its operating income. Total Assets Turnover of 2.66 indicates that, for every PhP1.00 of total assets there is PhP2.66 of sales revenue generated. Gross cost to gross income ratio that 0.55 implies that, for every PhP1.00 of gross income gross cost, PhP0.55 is earn and decreasing for every year of operation. The Cash payback period of the business is 0.21 or 2 months and 16 days can its investment coincide. Socio-Economic Feasibility Social economics focuses on the relationship between social behavior and economics. In general it analyzes how societies progress, stagnate or regress because of their local or regional economy, or the global economy. It will benefit those people who loves kakanin and also to the propose business. Its contribution may affect the growth of the economy. It emphasizes the social desirability of the project which focuses on reasonable economics benefits to the people living in the community as well is the government. CONCLUSION TO FEASIBILITY Based on the facts, data, analysis, and projected financial statements, the proponents conclude that the proposed business is feasible. The project researchers Danica L. Figuracion. Patricia Ann J. Manaligod, Mary Joy R. Setubal and K. C. Lyn F. Viray are positively looking over the success of the project and its feasibility on the proposed location based on the financial statement and financial ratio analysis
Thesis
Includes bibliographical references.
Keywords: Feasibility studies -- Tanay (Rizal, Philippines); Banana products